Fountain of Energy (Pacific Novelty Co.)
On verso: This is the work of A. Stirling Calder, and represents the completion of the Panama Canal. The earth rests on a pedestal in the center of a pool and is surmounted by the figure of Energy riding through the four oceans. Fame and Victory blow their bugles form shoulders.